ALTERNATIF DESAIN SPILLWAY PROYEK PEMBANGUNAN BENDUNGAN CIBEET KABUPATEN BOGOR PROVINSI JAWA BARAT - Trianto, Adden; Dwi Prasetyo, Ega; Ardhya Maharani, Shinta; Tunggulgeni, Ekodjati; Ahmad Fauzan, Sayed; Harianja, Ricky; Suprayogi, Suprayogi (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
Indonesia, as an agrarian country, heavily relies on the availability of water for irrigation, raw water supply, and electricity generation to support industrial growth. One of the government’s efforts to ensure water availability is the construction of dams, including the Cibeet Dam, which serves to reduce flooding, provide raw water, support irrigation, and generate electricity. A crucial component of a dam is the spillway, which must be capable of accommodating excess water, especially during extreme flood events. This study aims to re-evaluate the spillway design of the Cibeet Dam using a hydraulic and structural stability analysis approach. The data used includes the Cibeet Dam planning documents, topographic data, hydrological data, geotechnical data, soil investigation data, climatological data, and reservoir capacity data. The analysis covers stability against overturning, sliding, seepage, and soil bearing capacity under three water level conditions (empty, normal, flood), and assesses construction cost efficiency. The results show that reducing the spillway crest width by 0.5 m only increases the head (Hd) by 2 cm. The spillway with an ogee crest and USBR II stilling basin is considered stable, with safety factors >1.5 under normal conditions and >1.2 during seismic events. The soil bearing capacity is also deemed sufficient to support the structure under all water level conditions.